2009
DOI: 10.2746/042516409x464113
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of persistent dorsal displacement of the soft palate and evaluation of laryngohyoid position in 15 racehorses

Abstract: Racehorses with persistent DDSP can be treated successfully by laryngeal tie-forward or by laryngeal tie-forward followed by laser staphylectomy. Horses with persistent DDSP have a more caudal larynx and more caudal and dorsal basihyoid bone than horses with intermittent DDSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 13 publications
2
42
0
Order By: Relevance
“…In the horses, this reaction is observed after long, but not moderate, distance endurance rides and is characterised by a marked increase in SAA but not other acute phase proteins levels [26]. We have also reported that horses with pre-competition SAA levels higher than 1 mg/L failed to complete their long distance rides [25]. Thus, measuring the serum SAA concentration before entering a competition may indicate whether the horse is in poor condition, including subclinical disorders, overtraining or slight injuries that may worsen with exertion and lead to elimination from the ride [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the horses, this reaction is observed after long, but not moderate, distance endurance rides and is characterised by a marked increase in SAA but not other acute phase proteins levels [26]. We have also reported that horses with pre-competition SAA levels higher than 1 mg/L failed to complete their long distance rides [25]. Thus, measuring the serum SAA concentration before entering a competition may indicate whether the horse is in poor condition, including subclinical disorders, overtraining or slight injuries that may worsen with exertion and lead to elimination from the ride [25].…”
Section: Introductionmentioning
confidence: 99%
“…We have also reported that horses with pre-competition SAA levels higher than 1 mg/L failed to complete their long distance rides [25]. Thus, measuring the serum SAA concentration before entering a competition may indicate whether the horse is in poor condition, including subclinical disorders, overtraining or slight injuries that may worsen with exertion and lead to elimination from the ride [25]. Other authors have reported an increase in SAA concentration after moderate treadmill exercise during an experimental study on the effect of an antioxidative compound on exercise-induced muscle damage [27].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Laryngeal/hyoid position The relative positions of the larynx and hyoid apparatus is another speculated cause of DDSP supported by reports demonstrating a more ventrally located basihyoid bone in horses with DDSP as determined ultrasonographically, and horses with persistent DDSP have a more caudally located larynx than those with less severe, intermittent DDSP. 6,21 Furthermore, increased head and neck flexion increases the incidence of DDSP by a combination of increased negative pressures in the airway and caudal retraction of the larynx. 22,23 Improving the position of the larynx and hyoid apparatus is the basis of the laryngeal tie forward procedure, which aims to move the larynx dorsal and rostral and the basihyoid dorsal and caudal.…”
Section: Tongue Positionmentioning
confidence: 98%
“…5,[31][32][33] There is increasing support implicating laryngohyoid positioning as a factor associated with DDSP. 5,6,9,20,21,24,34 As such currently the most widely accepted surgical intervention, following failed conservative therapy, is laryngeal tie-forward with or without myectomy of the sternohyoideus and sternothyrohyoideus. Success rates approaching upward of 80% have been reported for this treatment strategy and there seems to be minimal detrimental effects to the horse.…”
Section: Update On Diseases and Treatment Of The Pharynxmentioning
confidence: 99%
See 1 more Smart Citation